Ignoring spatial effects results in inadequate models for variation in littoral macroinvertebrate diversity. Issue 6 (17th November 2016) - Tolonen, Kimmo T.; Vilmi, Annika; Karjalainen, Satu‐Maaria; Hellsten, Seppo; Sutela, Tapio; Heino, Jani
Abstract : Studies focusing on the effects of spatial processes versus environmental filtering on aquatic metacommunities have so far been focused almost entirely on relatively isolated systems, such as sets of different lakes or streams. In contrast, metacommunity patterns and underlying processes within a single aquatic system have received less attention. In this study, we aimed to examine how strongly variations in different diversity indices are affected by spatial processes (dispersal) versus local environmental conditions (species sorting) within a large lake system. Modern biodiversity research focuses on multiple diversity facets because different indices may be uncorrelated within and between facets, and they may thus describe different phenomena. We investigated the relationship of littoral macroinvertebrate diversity with environmental and spatial factors using 10 indices of species, functional and taxonomic diversity. Using spatial factors as proxies of dispersal, we decomposed variation in diversity indices into fractions attributable to environmental and spatial factors. Our results highlighted generally equal or higher importance of spatial processes in controlling the variation in diversity indices when compared to local environmental variables. Local environmental conditions accounted for higher proportion of variation only in a single index (i.e. taxonomic diversity). These findings suggest that the effects of high dispersal rates (mass effects) may override the influences of local environmental conditions (species sorting) on the diversity in highly‐connected aquatic system, such as large lakes and marine coastal systems. Our results further suggest that biodiversity assessment and environmental monitoring in highly‐connected systems cannot rely solely on the idea of environmental control. We hence recommend that the roles of both environmental and spatial processes should be integrated in basic and applied ecological research of aquatic systems.